Knowledge of Guideline VAP Bundle Improves Nurse Compliance Levels in Preventing Associated Pneumonia (VAP) Ventilation in the Intensive Care Unit - Siti Saodah (Universitas Muhammadiyah Semarang, 2019)
The use of mechanical ventilators is at risk of causing complications, Ventilator Associated Pnemonia (VAP). The Associated Pnemonia (VAP) Ventilator is a nosocomial infection that occurs in patients with Ventilator consumption from 48 hours. VAP prevention can be done with VAP bundle. The objective of this research to analyze the guidelines VAP bundle's knowledge relationship with the level of nurse compliance in VAP prevention. This type of research with cross sectional which describes the knowledge of VAP bundle of ICU-treatment. This study was conducted in March-April 2019 in the ICU Room of RS X in Semarang with a number of samples as many as 25 ICU nurses. Results indicate that there is a relationship of knowledge level to the level of nurse compliance in the implementation of VAP bundle in the ICU room of RS X in Semarang, the better the knowledge level, the better the level of compliance with P value 0.022 and r 0.456 which has the meaning there is a fairly strong relationship between levels of knowledge with the level of compliance of VAP bundle implementation. The nurses are expected to know and adhere to the VAP bundle so that the VAP does not occur against the mechanical ventilator attached patients.